2013
DOI: 10.1192/bjp.bp.112.112912
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of discrimination among people Using mental health services in England 2008-2011

Abstract: The proportion of participants experiencing no discrimination increased significantly over the course of TTC but by less than the initial target. The overall median discrimination score fell by 11.5%. Data from 2010 and 2011 suggest that these gains may be hard to maintain during economic austerity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
117
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(129 citation statements)
references
References 24 publications
7
117
2
Order By: Relevance
“…Allocation of participants to interviewers was based on interviewer availability. The detailed methodology is reported elsewhere (Hamilton et al 2011;Corker et al 2013;Henderson et al 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Allocation of participants to interviewers was based on interviewer availability. The detailed methodology is reported elsewhere (Hamilton et al 2011;Corker et al 2013;Henderson et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…'Get moving', 'Living libraries' and 'Education not discrimination' activities) Friedrich et al 2013). As part of the evaluation of TTC, and specifically to assess the effect of the programme on people with mental health problems, the Viewpoint survey was run annually to assess individuals' experience of discrimination within the previous 12 months (Henderson & Thornicroft, 2009;Henderson et al 2012;Corker et al 2013;Evans-Lacko, 2014a). Moreover, in the field of overcoming discrimination, it is important to assess service users' responses to discriminatory experiences, which constitute the process of coping (Mendoza-Denton et al 2006;Hinshaw, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies suggest that attitudes regarding working alongside someone with a mental illness are improving; employers surveyed in 2010 were less likely to say that workers with mental health problems faced negative attitudes from their colleagues compared to in 2006 and 2009 . However negative attitudes appear to considerably affect the way those with mental illness are treated in the workplace (Corker et al, 2013). It has been shown that those with mental illness experience being looked down on and treated as if they had low intelligence (Brohan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The Viewpoint survey found that health professionals are a frequent source of discrimination reported by those with mental illness (Corker et al, 2013) and patients have reported: being treated with disrespect; longer waits than other patients; and the suspicion that physical complaints are imagined (Schulze & Angermeyer, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Viewpoint (Hamilton et al 2011;Corker et al 2013) is an annual survey of mental health service users in England, which aims to evaluate outcomes of the Time to Change programme (Henderson & Thornicroft, 2009, the largest ever programme to reduce discrimination against people with mental health problems in England. Phase 1 of this programme aimed to achieve a 5% reduction in discrimination over 4 years through a national social marketing campaign launched in 2009, and national and local interventions which engaged individuals, communities and professional groups to improve the attitudes and behaviour of the general public towards people with mental health problems.…”
Section: Methodsmentioning
confidence: 99%